PRO: Biomarker surveillance for invasive fungal infections without antifungal prophylaxis could safely reduce antifungal use in acute leukaemia. Issue 4 (22nd July 2022) - Taynton, Thomas; Barlow, Gavin; Allsup, David
Abstract: Mould-active antifungal prophylaxis is frequently used to prevent invasive fungal infection in patients with acute leukaemia being treated with intensive chemotherapy. Invasive fungal infections are difficult to diagnose, and despite the use of prophylaxis a high proportion of patients still receive therapeutic antifungals. Antifungal medications have important interactions, can cause serious adverse events, and may drive the proliferation of antifungal resistance. The use of two biomarkers, such as galactomannan in combination with the less-specific β-d -glucan, can mitigate the risk of not detecting non- Aspergillus species, as well as improving pooled sensitivity and specificity. We argue that regular biomarkers could be used safely as part of an antifungal stewardship strategy to reduce antifungal use, by both screening for infection in patients not on prophylaxis and ruling out infection in patients treated empirically.